2006
DOI: 10.1099/ijs.0.64138-0
|View full text |Cite
|
Sign up to set email alerts
|

Ornithinimicrobium kibberense sp. nov., isolated from the Indian Himalayas

Abstract: A buff-yellow-pigmented bacterium, strain K22-20 T , which was isolated from a cold desert of the Indian Himalayas, was subjected to a polyphasic taxonomic study. Phenotypic and chemical properties of strain K22-20 T were consistent with its classification in the genus Ornithinimicrobium.The major fatty acids of the strain were iso-C 17 : 1 v9c (cis-15-methyl 7-hexadecenoic acid), iso-C 15 : 0 (13-methyl tetradecanoic acid), iso-C 16 : 0 (14-methyl pentadecanoic acid) and iso-C 17 : 0 (15-methyl hexadecanoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 25 publications
3
50
1
Order By: Relevance
“…Sensitivity of the strain to antibiotics was tested by using antibiotic susceptibility discs (HiMedia, India) after incubation for 48 h. Acid production from various sugars was tested in minimal medium as described by Smith et al (1952). Oxidation of various substrates was determined by using biolog GN2 microplates (BIOLOG Inc.) as described by Mayilraj et al (2006). Enzyme activities were determined using the API ZYM tests (bioMérieux).…”
Section: Morphological Physiological and Biochemical Characterizationmentioning
confidence: 99%
“…Sensitivity of the strain to antibiotics was tested by using antibiotic susceptibility discs (HiMedia, India) after incubation for 48 h. Acid production from various sugars was tested in minimal medium as described by Smith et al (1952). Oxidation of various substrates was determined by using biolog GN2 microplates (BIOLOG Inc.) as described by Mayilraj et al (2006). Enzyme activities were determined using the API ZYM tests (bioMérieux).…”
Section: Morphological Physiological and Biochemical Characterizationmentioning
confidence: 99%
“…There are reports of getting Rhodococcus spp. from Pindari glacier (Shivaji et al, 2011), Antarctic sediments (Muangchinda et al, 2014), cold desert of the Himalayas (Mayilraj et al, 2006), and Arctic glacier (Reddy et al, 2009). Pham et al, (2014) reported on the role in bioremediation at cold habitats by Rhodococcus strains.…”
Section: Effects Of Production Parameters On Lipase By N149 and Y-32mentioning
confidence: 99%
“…The selected strains were identified by 16S rRNA gene sequencing. Genomic DNA extraction and amplification was performed as previously described [22]. Identification of phylogenetic neighbours and the calculation of pairwise 16S rRNA gene sequence similarities were achieved using the EzTaxon server [23] and alignment was carried out using Mega version 6.0 [24].…”
Section: Bacterial Strain Isolation and Identificationmentioning
confidence: 99%